2012
DOI: 10.1167/iovs.12-10283
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Bevacizumab Treatment on Newborn Rat Retinal Cell Proliferation, Death, and Differentiation

Abstract: PURPOSE. Vascular endothelial growth factor (VEGF) is an important signal protein in vertebrate nervous development, promoting neurogenesis, neuronal patterning, and glial cell growth. Bevacizumab, an anti-VEGF agent, has been extensively used for controlling pathological retinal neovascularization in adult and newborn patients, although its effect on the developing retina remains largely unknown. The purpose of this study was to investigate the effect of bevacizumab on cell death, proliferation, and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
7
0
7
Order By: Relevance
“…[176] There is some limited data to suggest that anti-VEGF agents may cautiously be used in developing retinae: bevacizumab did not induce any changes in cell death or proliferation in early developing rat retinal explants maintained in organotypic culture, [176] and no electroretinographic or morphological abnormalities were detected in 11- or 35- day old rabbits who received intravitreal injections of bevacizumab. [177] Given the importance of vasculature in retinal function, more thorough investigation of the developmental toxicology of angiogenesis inhibitors is certainly warranted before they are pursued as retinoblastoma therapeutics.…”
Section: Pre-clinical Progress In Retinoblastoma Therapeuticsmentioning
confidence: 99%
“…[176] There is some limited data to suggest that anti-VEGF agents may cautiously be used in developing retinae: bevacizumab did not induce any changes in cell death or proliferation in early developing rat retinal explants maintained in organotypic culture, [176] and no electroretinographic or morphological abnormalities were detected in 11- or 35- day old rabbits who received intravitreal injections of bevacizumab. [177] Given the importance of vasculature in retinal function, more thorough investigation of the developmental toxicology of angiogenesis inhibitors is certainly warranted before they are pursued as retinoblastoma therapeutics.…”
Section: Pre-clinical Progress In Retinoblastoma Therapeuticsmentioning
confidence: 99%
“…48 Neurocan is synthesized normally by neurons 49 but also by reactive glial cells. 50,51 Since Miguel et al 26 found changes in retinal glial maturation produced by bevacizumab, it is possible that such abnormality contributed to the reduced neurocan content observed in our study.…”
Section: Discussionmentioning
confidence: 69%
“…The subject is important since VEGF, which is expressed by astrocytes in the retinal tissue during its development, 44,45 apparently acts as a neuroprotective and neurotrophic factor for retinal cells, influencing neuronal growth, differentiation, and survival. 7,23 Thus, Miguel et al 26 observed changes in glial maturation with upregulation of vimentin and downregulation of GFAP mRNA in retinal explants of newborn rats treated with bevacizumab for 2 days in vitro compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As AMD affected mainly the central region, changes were expected in R1, which had the largest concentration of retinal neurons affected by the disease and was the place where the drug's anti-angiogenic effect was expectedly higher (4) . Some experimental studies suggested a possible toxic effect of high-dose intravitreal VEGF inhibitors on retinal neurons (29,30) . The lower retinal electrical activity observed immediately after treatment raised the possibility of a deleterious effect of the medication on macular function, which fortunately recovered over time.…”
Section: Discussionmentioning
confidence: 99%